2012
DOI: 10.1063/1.4749248
|View full text |Cite
|
Sign up to set email alerts
|

A new four-dimensional ab initio potential energy surface for N2O–He and vibrational band origin shifts for the N2O–HeN clusters with N = 1–40

Abstract: A new four-dimensional ab initio potential energy surface for N(2)O-He is constructed at the CCSD(T) level with an aug-cc-pVQZ basis set together with bond functions. The vibrational coordinates Q(1) and Q(3) of N(2)O are explicitly included, due to the strong coupling between the symmetric and asymmetric stretches of N(2)O. A global potential energy surface is obtained by fitting the original potential points to a four-dimensional Morse∕long range (MLR) analytical form. In the fitting, the ab initio noise in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 42 publications
0
25
0
Order By: Relevance
“…89 This involved some experimentation to ascertain the most appropriate choice for the integer parameter p and q and the factor f ref appearing in the definitions of the radial variables y (20) and (22), and for the order N of the exponent polynomial of Eq. (21). As pointed out above, the present potential function model used p = 5, q = 3, and f ref = 1.2, and the exponent polynomial order was N = 4 .…”
Section: B Least-squares Fitsmentioning
confidence: 99%
“…89 This involved some experimentation to ascertain the most appropriate choice for the integer parameter p and q and the factor f ref appearing in the definitions of the radial variables y (20) and (22), and for the order N of the exponent polynomial of Eq. (21). As pointed out above, the present potential function model used p = 5, q = 3, and f ref = 1.2, and the exponent polynomial order was N = 4 .…”
Section: B Least-squares Fitsmentioning
confidence: 99%
“…4 Species such as CO 2 , OCS, N 2 O, and CS 2 belong to a class and have similar properties, due to their isovalent electrons. Except for Rg-CS 2 (Rg = He, Ne, Ar, Kr, and Xe) complexes, the complexes consisting of such species (CO 2 , a) Electronic addresses: zhenglimin@wipm.ac.cn; cxduan@phy.ccnu.edu.cn; yplu@ntu.edu.sg OCS, N 2 O) and rare gas atoms have received much attention in both experimental [5][6][7][8][9][10][11][12] and theoretical studies, [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31] due to their fundamental nature and practical importance. In experiment, the microwave and infrared spectra for these complexes were reported widely [8][9][10][11][12] and showed that each complex has a T-shaped structure.…”
Section: Introductionmentioning
confidence: 99%
“…In theoretical calculations, many ab initio potential energy surfaces for these complexes have been available in literatures. [16][17][18][19][20][21][22][23][24][25][26][27][28][29] Very similar features are found on their PESs, such as the global "T-shaped" minimum, local linear minima, and saddle points. The intermolecular interactions in these complexes vary systematically with both the polarizability of the rare gas atoms and with the electronic structures of the linear molecules.…”
Section: Introductionmentioning
confidence: 99%
“…One possible reason of the large discrepancy is that only a 1D intramolecular coordinates used in the construction of PES. For He van der Waals dimer with N 2 O, it has been proved that the two-dimensional intramolecular coordinates would improve the accuracy of PES [33]. We fitted the rotational energy levels of Kr-N 2 O with the Watson asymmetric rotor Hamiltonian employing the A-type reduction in the Ir representation,…”
Section: Comparison With Experimentsmentioning
confidence: 99%